Di Tengah Euforia Digitalisasi Pelayanan Publik di Kabupaten: Memunculkan Penerimaan Masyarakat - Wargadinata, Ella Lesmanawaty; Tendean, Noudy R. P. (Jurnal Bina Praja, 2024)
Information and communication technology was used for two decades to elevate good governance practices under Indonesia's bureaucratic reform policy. With the fast-expanding use of the internet, all government organizations are being pushed to implement digital public services to eliminate rigid procedures. The purpose of the research is to reveal factor affecting public perception’ and acceptance on digital public services using qualitative approach with Technology Acceptance Model as a basic framework. Data collected from 13 public service applications in different areas, gathered through: 13 municipal information and communication’ officials, interviews with 38 conventional public service applicants, 282 digital services users, the policies-regulations as secondary data, those analyzed by Nvivo and visualized on hierarchy chart. It is clear that while becoming digitized is an ambitious agenda, there are wide gaps among municipalities: geographical landscape, technology infrastructure, financial and human resources. On the public side, a majority remained stick to conventional services, primarily due to non-technology factors: their comfort with traditional processes, the perceived complexity of the application, their digital literacy, experiences, economic-societal barriers, all of which emerged as barriers to digital services acceptance. Injecting digital technology in the public sector is inevitable. However, It is necessary to build community digital readiness despite technology infrastructure and official capabilities, especially in peripheral local governments